Penciptaan Busana dengan Sumber Ide Rumah Adat Suku Tengger - Susi Gomes; Inty Nahari; Imami Arum Tri Rahayu; Lutfiyah Hidayah (Universitas Palangka Raya, 2024)
The creation of this work is based on the type of Practice-Ed Research approach carried out through a study of fashion design practices with a focus on